"Take My License n' All That Jive, I Can't See … 35": Little Hope for the Future Encourages Offending Over time. (2nd January 2016) - Piquero, Alex R.
Abstract : A very small number of studies has observed that persons who perceive an early age-at-death report a higher risk of offending. This literature, however, is limited by the use of general population samples, cross-sectional data, and the failure to consider both the determinants of perceived age-at-death, as well as some of the mediating processes associated with the relationship between perceived age-at-death and offending. Using data for a large sample of serious youthful offenders from two urban cities and who were followed for seven years, the current study attends to these concerns. Results show that gender, race/ethnicity, and adverse neighborhood conditions influence the perceived age-at-death; this perception distinguishes between distinct trajectories of offending, and such perceptions also influence both perceived risks and perceived rewards as well as one's impulse control.